Analytical Hierarchy Process for Enhancing Procurement Decision-Making in Project Phase: A Case Study in the Gold Mining Project - Budi Irawan Saleh; Choirul Anwar; Rusman Zaenal Abidin; Aris Setyo Radyawanto (ComTech: Computer, Mathematics and Engineering Applications, 2020)
The aim of the research was to enhance the selection for the process plant equipment supplier based on their country of origin in the gold mining project using the Analytical Hierarchy Process (AHP). The research also intended to investigate how AHP could further enhance the process of the project. The steps for modeling the AHP were identifying the hierarchy by the project team, constructing the AHP model, and calculating the weight for supplier selection. The research object was a gold mining company based in Indonesia. The schedule and resources were calculated, followed by a survey to evaluate the AHP process. After modeling and calculating using AHP, it is found that the three highest criteria for selecting the process plant equipment suppliers are running capacity (14,3 %), efficiency (9,9%), and endurance (9,7%). The overall scores for each supplier show that supplier from United States (25,87%) is in the first rank. It is followed by Germany (25,80%) and Australia (25,20%). Moreover, AHP is proven to enhance the process by not only reducing the time of decision-making for two days but also increasing the resource by almost 23%. Based on the survey to the project team, AHP increases the involvement of the project team in the decision-making process and shows that more than 80% of the project team agrees with the decision. The survey also reveals that almost 63% of the project team decides to use the same tools for the decision-making process.